First detection of African swine fever (ASF) virus genotype X and serogroup 7 in symptomatic pigs in the Democratic Republic of Congo - Bisimwa, P.N.; Ongus, J.R.; Tiambo, Christian K.; Machuka, Eunice M.; Bisimwa, E.B.; Steinaa, Lucilla; Pelle, Roger (Springer, 2020)
Background African swine fever (ASF) is a highly contagious and severe hemorrhagic viral disease of domestic pigs. The analysis of variable regions of African swine fever virus (ASFV) genome led to more genotypic and serotypic information about circulating strains. The present study aimed at investigating the genetic diversity of ASFV strains in symptomatic pigs in South Kivu province of the Democratic Republic of Congo (DRC). Materials and methods Blood samples collected from 391 ASF symptomatic domestic pigs in 6 of 8 districts in South Kivu were screened for the presence of ASFV, using a VP73 gene-specific polymerase chain reaction (PCR) with the universal primer set PPA1-PPA2. To genotype the strains, we sequenced and compared the nucleotide sequences of PPA-positive samples at three loci: the C-terminus of B646L gene encoding the p72 protein, the E183L gene encoding the p54 protein, and the central hypervariable region (CVR) of the B602L gene encoding the J9L protein. In addition, to serotype and discriminate between closely related strains, the EP402L (CD2v) gene and the intergenic region between the I73R and I329L genes were analyzed. Results ASFV was confirmed in 26 of 391 pigs tested. However, only 19 and 15 PPA-positive samples, respectively, were successfully sequenced and phylogenetically analyzed for p72 (B646L) and p54 (E183L). All the ASFV studied were of genotype X. The CVR tetrameric repeat clustered the ASFV strains in two subgroups: the Uvira subgroup (10 TRS repeats, AAAABNAABA) and another subgroup from all other strains (8 TRS repeats, AABNAABA). The phylogenetic analysis of the EP402L gene clustered all the strains into CD2v serogroup 7. Analyzing the intergenic region between I73R and I329L genes revealed that the strains were identical but contained a deletion of a 33-nucleotide internal repeat sequence compared to ASFV strain Kenya 1950. Conclusion ASFV genotype X and serogroup 7 was identified in the ASF disease outbreaks in South Kivu province of DRC in 2018–2019. This represents the first report of ASFV genotype X in DRC. CVR tetrameric repeat sequences clustered the ASFV strains studied in two subgroups. Our finding emphasizes the need for improved coordination of the control of ASF.